2022
DOI: 10.1029/2022sw003110
|View full text |Cite
|
Sign up to set email alerts
|

Solar Cycle Variability in Coronal Holes and Their Effects on Solar Wind Sources

Abstract: Various upstream spacecraft have now observed the solar wind conditions affecting the Earth since the 1970s, covering over four solar activity cycles. These measurements provide a long term picture of the related patterns in large scale incident plasma and magnetic field parameters of interest for both interpreting cycles in geospace effects, and understanding how the Sun controls our space environment. This paper focuses on the latter, in part to provide context at the start of the new solar cycle 25, and tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The effects of differential rotation (faster solar rotation at equator than higher latitudes) can be seen in the drift of the equatorial portion of both coronal holes to the right (the equator rotates prograde relative to the synoptic Carrington rate of 27.3 days; see discussion in Luhmann et al. (2022)) (right column) Solar wind at Earth versus time (top) and related wavelet (bottom) showing periodic solar wind 7–9 day forcing. Data from https://omniweb.gsfc.nasa.gov/.…”
Section: Evolution Of a Solar Minimummentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of differential rotation (faster solar rotation at equator than higher latitudes) can be seen in the drift of the equatorial portion of both coronal holes to the right (the equator rotates prograde relative to the synoptic Carrington rate of 27.3 days; see discussion in Luhmann et al. (2022)) (right column) Solar wind at Earth versus time (top) and related wavelet (bottom) showing periodic solar wind 7–9 day forcing. Data from https://omniweb.gsfc.nasa.gov/.…”
Section: Evolution Of a Solar Minimummentioning
confidence: 99%
“…The level of participation increased with its expanded scope, encompassing Sun to solar wind to planetary magnetospheres and atmospheres. The articles accompanying this introduction (Allen et al, 2023;Badman et al, 2023;Bregou et al, 2022;Gasperini et al, 2023;Hewins et al, 2023;Hudson et al, 2021;Lloveras et al, 2022;Luhmann et al, 2022;Mlynczak et al, 2022;Palmerio et al, 2022;Riley et al, 2022;Varela et al, 2022;Younas et al, 2022) represent the beginnings of analyses that are likely to continue for years to come.…”
Section: A Brief History Of the "Whole Intervals"mentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, only a few studies have evaluated the effects of space weather on aviation by systematically considering space weather, satellite navigation, and ATM together. In previous studies, Solar activity has shown an 11-year cycle (Luhmann et al, 2022;Swiger et al, 2022). The annual mean total sunspot number since 1900 is illustrated in Figure 1.…”
mentioning
confidence: 91%
“…As such, changes in the average shape and structure of the corona in time have often been characterized in a variety of models on CR-to-CR basis, ranging from simple potential field source surface (PFSS) extrapolations to full magnetohydrodynamic (MHD) calculations. In this modeling paradigm, successive monthly "snapshots" of the corona are computed separately, with each calculation for a given CR being fully independent of the previous case (e.g., Riley et al 2006;Luhmann et al 2022).…”
Section: Introductionmentioning
confidence: 99%